2017
DOI: 10.1007/s10943-017-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Religious Coping and Self-Care Behaviors in Iranian Medical Students

Abstract: In recent years, researchers have identified that coping strategies are an important contributor to an individual's life satisfaction and ability to manage stress. The positive relationship between religious copings, specifically, with physical and mental health has also been identified in some studies. Spirituality and religion have been discussed rigorously in research, but very few studies exist on religious coping. The aim of this study was to determine the relationship between religious coping methods (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The situational context must also be consideredthe intensity of the pandemic is much lower in Poland, which does not preclude humor as a dominating coping strategy. Iranian society is very religious, leading to religious coping being a common self-care behavior [28] and spiritual-religion psychotherapy being widely employed to ameliorate the consequences of stress [29]. Religion is a personal matter in Poland, whereas in Iran, people often turn to a transcendental force for support during crises.…”
Section: Discussionmentioning
confidence: 99%
“…The situational context must also be consideredthe intensity of the pandemic is much lower in Poland, which does not preclude humor as a dominating coping strategy. Iranian society is very religious, leading to religious coping being a common self-care behavior [28] and spiritual-religion psychotherapy being widely employed to ameliorate the consequences of stress [29]. Religion is a personal matter in Poland, whereas in Iran, people often turn to a transcendental force for support during crises.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Jafari et al (2015) which was conducted on patients with type 2 diabetes, a significant relationship was found between religious orientation and self-care. Sharif Nia et al (2017) also demonstrated an independent significant association between positive religious coping and self-care behaviors in patients with chronic illness.…”
Section: Introductionmentioning
confidence: 89%
“…Then, the relationship between thickness and precursor concentration was also explored after the optimized temperature was confirmed. Finally, the results were analyzed by mathematical statistics and tested by Student’s t -test [16,17]. …”
Section: Methodsmentioning
confidence: 99%